Synthesis, radiolabeling with fluorine-18 and preliminary in vivo evaluation of a heparan sulphate mimetic as potent angiogenesis and heparanase inhibitor for cancer applications. Issue 6 (13th January 2016) - Kuhnast, B.; El Hadri, A.; Boisgard, R.; Hinnen, F.; Richard, S.; Caravano, A.; Nancy-Portebois, V.; Petitou, M.; Tavitian, B.; Dollé, F.
Abstract : A rationally designed, fully synthetic, octasaccharide-based, HS mimetic has been synthesized, in vitro characterized, labeled with fluorine-18, and in vivo imaged with PET in rats. Abstract : Heparan Sulfate (HS) mimetics are able to block crucial interactions of the components of the extracellular matrix in angiogenic processes and as such, represent a valuable class of original candidates for cancer therapy. Here we first report the synthesis and in vitro angiogenic inhibition properties of a conjugated, novel and rationally-designed octasaccharide-based HS mimetic. We also herein report its labeling with fluorine-18 and present the preliminary in vivo Positron Emission Tomography imaging data in rats. This constitutes one of the rare examples of labeling and in vivo evaluation of a synthetic, polysaccharide-based, macromolecule.